An Inquiry on the Principles of Optional-Narrator Theory - Hallaçi, Arta (Respectus Philologicus, 2026)
This article presents the findings of a survey examining the principles proposed by Optional-Narrator Theory: Principles, Perspectives, Proposals (2021) in relation to literary instruction. The data from the questionnaire delivered to BA and MA students in the role of readers confirms some proposals of the optional-narrator theory. As the number of literature courses increases, students (in the function of readers) seem obligated to assign a fictional voice that speaks in a poem, even in poems that do not use one, thus confirming the optional-narrator theory’s claim that academia often insists on an abundant literary terminology. Another proposal of the optional-narrator theory, confirmed by this paper, is that the obligatory focus on fictional voices shifts the reader’s attention away from the poet’s aesthetic achievements (students found it difficult to attribute rhyme and meter to the poet). Although the study reconfirms that literary instruction positively affects the development of skills in identifying narrative concepts, the results also suggest that the claims of optional-narrator theory are valid and useful to the future of literary instruction and academia, as we once again turn our attention back to the pivotal role of the author.